Controllability of Neutral Fractional Functional Equations with Impulses and Infinite Delay - R. Ganesh; R. Sakthivel; Yong Ren; S. M. Anthoni; N. I. Mahmudov (Abstract and Applied Analysis)
We examine the controllability problem for a class of neutral fractional integrodifferential equations with impulses and infinite delay. More precisely, a set of sufficient conditions are derived for the exact controllability of nonlinear neutral impulsive fractional functional equation with infinite delay. Further, as a corollary, approximate controllability result is discussed by assuming compactness conditions on solution operator. The results are established by using solution operator, fractional calculations, and fixed point techniques. In particular, the controllability of nonlinear fractional control systems is established under the assumption that the corresponding linear control system is controllable. Finally, an example is given to illustrate the obtained theory.